The Urgency of Free Health Service Policy in Increasing Indonesia's Human Development Index - Aceng Ali Awaludin; Restu Widyo Sasongko; Pande Ayu Naya Kasih Permatananda; Heppi Syofya; Untung Gunawan (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study is a qualitative study with a descriptive approach, namely an approach that details one by one using descriptive text on each main topic used in this article, including Health, Human Development Index, and Free Health Check Policy. The data used in this study are secondary data that researchers obtain from second sources or indirect sources. Although obtained from indirect sources, researchers still select the research sources obtained and it can be ensured that the sources used by researchers are reliable. The research sources used in this study include books, scientific articles, magazines, and various other sources used in each study. The data obtained were analyzed by the stages of data collection, data reduction, data selection, and drawing conclusions.